Tingkat Resiliensi dengan Ide Bunuh Diri Pada Remaja - Kania Febrya Putri; Duma Lumban Tobing (UIMA Press, 2020)
Introduction: World Health Organization (WHO) had claimed suicide as the second-leading cause of death among 15- to 26-year-olds in 2016. Emotion dysregulation might impact suicidal ideation among adolescents. To prevent suicidal thoughts and suicide, the literature suggested to increase resilience ability. This ability would help adolescent adapted to the environmental changes properly. Objective: . The aims of this research was to analyze the correlation of resilience, age, gender, marital status of parents, and suicidal ideation among adolescents. Design: .Two hundred and thirty one participants age ranged 15-17 were recruited for this research. Data on demographic was collected and participants would be asked to solve Connor Davidson Resilience Scale (CD-RISC) and Suicidal Ideation Questionnaire (SIQ). Result: This research revealed the correlation found between resilience and suicidal ideation. Suicidal ideation also can be found in adolescents with non-divorced parents and moderate resilience. Conclusion: Fostering and increasing resilience ability might be important effort to prevent and reduce suicidal ideation among adolescents.